(untitled) (Journal of the Management Sciences, 2024)
In the age of rapid technological advancements, digital transformation has become a defining force reshaping global sectors. The Nigerian public service, as a fundamental element of the country’s administrative framework, is no exception. This study delved into the multifaceted challenges and opportunities that arise when implementing digital transformation in the Nigerian public service. Despite its importance, the public service has long grappled with inefficiency, corruption, and service delivery issues. Digital transformation, facilitated by technologies like AI and data analytics, presents a solution to these problems. This research adopted a qualitative approach, gathering data from secondary sources including journals and online resources while using Technology Acceptance Model (TAM), originally proposed by Davis in 1989 as a guide. The study focused on the integration of digital technologies in administrative processes and examined its dimensions in the contemporary context. Digital transformation offers the Nigerian public service numerous advantages, including streamlined service delivery, transparency, data-driven decision-making, citizen engagement, remote access, and cost savings. However, several barriers impeded its adoption. Infrastructure deficit in rural areas limits equitable access to digital services. A lack of digital skills among employees and leadership gaps hinder seamless integration. Frequent power outages disrupt digital initiatives, while political dynamics, inadequate policies, and resistance slow progress. Theft and vandalization of infrastructure exacerbate challenges. To advance digital transformation in Nigeria, a comprehensive approach is required. Prioritizing telecommunications and internet infrastructure in rural areas, establishing training programs, investing in reliable power supply, creating secure digital databases, formulating supportive policies, and enhancing security measures around critical infrastructure are essential steps. Successful implementation of these recommendations can pave the way for improved efficiency, transparency, and service delivery in the Nigerian public service, while also serving as an example for similar endeavors in the region.